Potencial Evocado Auditivo de Tronco Encefálico por Frequência Específica em lactentes do nascimento aos três meses de idade - Almeida, Mabel Gonçalves (2009)
The frequency specific auditory evoked potential can give contribuitions in the diagnosis of hearing infants when it is not possible to assess the hearing levels thraugh behavioral and conditioned tests.allowing the estimation of hearing sensitivity to different frequencies of the audiogram and therefore guide the pracess of hearing aids selection and following contrais. Purpose. To describe the findings for the frequency specific auditory brainstem response in hearing infants. from birth to three months. Method. We evaluated 23 infants without risk indicators for hearing loss according to the JCIH (2007) with average chranological age of 2 months and 10 days. The infants had a TEOAE and AABR present in both ears and type A tympanometry. The analysis compared the minimal levei response and absolute latencies for wave V, according to sex, and for the four frequencies studied. Results.There was no significant differences in latencies for the minimal levei response according to to the sexo The FE- ABR thresholds were 34.2 dB HL (+_ 11.0) for the stimulus toneburst in the frequency of 500 Hz, 25.4 dB HL (+_ 8, 3) for the frequency of 1000 Hz, and for 2000 and 4000 Hz were of 19 dB HL (+_ 5.5) and 17.5 dB HL (+_ 6.4) respectively. The absolute latencies for wave V for 70 dB and 20 dB HL,: respectively, in response to 500 Hz was 10.75 ms and 15.2 ms; in response to 1000 Hz was 8.9 ms and 13.4 ms; for the frequency of 2000 Hz was 7.7 ms and 10.2 ms; ànd for the frequency of 4000 Hz was 7.3 ms and 9.4 ms. Contlusion. It was concluded that the tone-burst ABR assists in the diagnosis of audiological estimate the hearing sensitivity at frequencies of 500 Hz, 1000 Hz, 2000 Hz and 4000 Hz, can be used in clinical practice for hearing evaluation of children who do not respond in a reliable manner to behavioral assessment